Penggunaan Media Pop-Up Book dengan Pendekatan Saintifik untuk Mengatasi Kesulitan Menulis Teks Deskripsi di SD - Putri, Atikah; Adina, Aisyah; Habibi, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Writing descriptive text is one of the basic literacy skills that elementary school students must master. However, many students still experience difficulties in developing ideas, choosing appropriate vocabulary, and organizing sentences coherently. This study aims to identify students’ difficulties in writing descriptive texts, describe the concept and implementation of Pop-Up Book media with a scientific approach, and synthesize findings from previous studies regarding the effectiveness of their integration. This study employed a Systematic Literature Review (SLR) method with a descriptive qualitative approach. Literature searches were conducted through Google Scholar, Semantic Scholar, and ResearchGate using relevant keywords, resulting in 45 initial articles that were later screened into 15 articles based on predetermined inclusion and exclusion criteria. The findings indicate that the use of Pop-Up Book media integrated with the scientific approach (5M: observing, questioning, experimenting, reasoning, and communicating) had a significant effect on improving students’ descriptive writing skills. Students became better at developing ideas, using varied vocabulary, and producing more structured writing.